Selecting age-specific protocol for controlled ovarian hyperstimulation in IVF program with particular reference to advanced age group - Anjana Ray Chaudhuri; Siddhartha Chatterjee (Al Ameen Medical College, 2013)
Aim: The present study was aimed at finding out the age specific best protocol for ovarian stimulation, particularly for advanced age group. Materials and Methods: This retrospective analysis was carried out from July 2005 to June 2009 in 617 cycles of In-vitro Fertilization (IVF) in different age group patients, performed at our centre. 617 patients having indications for female factor infertility were randomly divided into 3 age groups, as 26 to 30 years (younger age group); 31 to 35 years (middle age group) and 36 to 40 years (advanced age group). They were selected for IVF program, after routine investigations. 4 different stimulation protocols, e.g., Long Down Regulation (LDR), Ultra Long Down Regulation (ULDR), Soft Stimulation (SS) Protocol and Antagonist Protocol utilized were analyzed primarily on the basis of the amount of Gonadotrophin (Gn) ampoules required for ovarian stimulation, terminal estradiol (E2) value, oocyte recovery rate, clinical pregnancy rate (PR) and take home baby rate (THBR). Results: LDR was proved to be the protocol of choice for all the other groups except advanced age group where SS proved to be the best with antagonist protocol being the close follower. Conclusion: As least amount of ovarian stimulation is used in SS, it is cost effective and imposes minimum risk of ovarian hyperstimulation syndrome (OHSS) and offers maximum PR for advanced age group patients, and reasonable PR for other age groups.